Does competition enhance the double-bottom-line performance of microfinance institutions? - Hossain, Shahadat; Galbreath, Jeremy; Hasan, Mostafa Monzur; Randøy, Trond (Journal of Banking & Finance, 2020)
This paper investigates how competition affects the double-bottom-line performance of microfinance institutions (MFIs). While classical economic theory highlights that competition enhances efficiency and benefits both customers and firms, we argue that this is unlikely to apply to institutions operating in socially oriented industries, such as microfinance. Using a cross-country dataset of 4576 MFI-year observations (1139 unique MFIs) operating in 59 countries over a 10-year period (2005-2014), we find that competition has an adverse effect on MFIs’ economic sustainability and that competition undermines their breadth of outreach but enhances their depth of outreach. These results are robust to alternative specifications of competition and to the use of a two-stage least squares (2SLS) analysis to alleviate the endogeneity concern. The findings from our analysis have important implications when considering the regulation of MFI competition, especially in the light of the recent turmoil of MFI markets in some developing countries.